EDUKASI KEWIRAUSAHAAN DENGAN LOMBA BUSINESS MODEL CAMPAS - syafril, syafril; Hidayat, Taufik; Mohdari, Mohdari; Hayati, Diana (JCSE: Journal of Community Service and Empowerment, 2024)
Becoming an entrepreneur is not a choice for many Indonesians.  Most Indonesians prefer to become a civil servant or private employee as their main priority.  This is inseparable from the mindset and upbringing of most Indonesians who see that an employee has no risks, whereas entrepreneurship is full of risks and financial uncertainty.  Very few people dare to take the risk of becoming an entrepreneur because there is no certainty of income and business success.  In the midst of increasingly difficult competition to obtain employee status, the way out is to become an entrepreneur.  To become an entrepreneur, the government and the world of education are trying to educate their students with various business knowledge so that they become entrepreneurs after graduating.  This activity is a form of Community Service that must be carried out by lecturers in fulfilling the Tri Dharma of Higher Education, namely Teaching, Service and Research.  The methods used in this service are presentations, discussions, competitions and activity evaluation. It is hoped that the results of this activity will stimulate students' desire to become entrepreneurs when they graduate